Development and validation of the Chinese school environment influencing physical activity habits scale - Dai, Shengting; Wu, Yang; Yan, Jingfei; Zeng, Li (Frontiers in Education, 2025)
IntroductionRegular physical activity is essential for preventing overweight and obesity in children and adolescents while also enhancing mental well-being. For teenagers, behaviors are predominantly shaped by habits, highlighting the importance of fostering positive physical activity practices. Schools, as central to adolescents’ daily routines, play a critical role in influencing students’ lifestyles and activity levels.MethodsThis study aimed to develop and validate a measurement instrument tailored to the Chinese social context to assess the impact of school-based factors on adolescents’ physical activity habits. A sample of 1,061 students was recruited through stratified cluster sampling from 24 secondary schools across six provinces in China. Following data cleaning, 1,004 valid responses were analyzed. The sample was divided into two subsets: one (n = 502) for exploratory factor analysis (EFA) and one (n = 502) for confirmatory factor analysis (CFA).ResultsEFA identified four factors comprising 19 items: Facility Environment Attraction (5 items), Specification of Teachers’ Competence (5 items), Influence of Peer Relationships (5 items), and Guarantee of Curriculum Setting (4 items). The factors demonstrated strong internal consistency (Cronbach’s alpha: 0.841–0.895). CFA confirmed the scale’s validity with an acceptable model fit (CMIN/DF = 3.888, TLI = 0.904, SRMR = 0.043, RMSEA = 0.046, GFI = 0.918). Additionally, the scale exhibited high internal consistency and test–retest reliability.DiscussionThis validated instrument provides researchers with a robust tool to evaluate school-related influences on physical activity habits among Chinese adolescents. The findings offer practical insights for promoting healthy behaviors, improving physical and mental health, and fostering holistic well-being in this population.